PARTISIPASI PEREMPUAN DALAM PROGRAM PEMBERDAYAAN MASYARAKAT BERBASIS RUKUN WARGA (PMB-RW) DI KELURAHAN TUAH KARYA KECAMATAN TAMPAN KOTA PEKANBARU - Juniazti, Tisa; Harahap, Tuti Khairani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Society Empowerment Program based Hamlet (PMB-RW) was one of construction program provided by government of Pekanbaru city. This program purposed to empower all society started from a Hamlet (RW). The implementation of this program had needed participation from society in order to achieve a program purpose. The participation of this program was men and women. In 2015, this program can reach socialization stage in form was training. The training had done needs a woman as the main participation. The main participation in the training was woman.This function of this research was to determine woman’s participation in PMB-RW program. The woman’s participation were training and the influence factors of woman’s participation in Tuah Karya district. The training was include a sewed training, a cooking training and tambourine.The concept theory used by researcher was a participation theory created by Sutoro Eko, society empowerment, decentralization and gender. This research was qualitative and descriptive research that had purposes to give a systematical and factual description about woman participation in program implementation. The collection of data in this research was using an interview, an observation and documentation.The result of this research showed that a woman had participate in PMB-RW program especially in training implementation of Tuah Karya district. Some factors that influence the participation were from intern factors such as; the willingness/awareness and occupation. Besides, from extern factor are the leadership and facility factor.Key words: woman’s participation, society empowerment.